2020
DOI: 10.2741/4808
|View full text |Cite
|
Sign up to set email alerts
|

A new backpropagation neural network classification model for prediction of incidence of malaria

Abstract: Spiking BPNN for malaria incidence prediction 300

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a study for prediction of the incidence of malaria, researchers used a new back-propagation neural network (BPNN) classification model. They showed that BPNN model was well suited for deciphering the risk of acquiring malaria as well as other infectious diseases [ 64 ]. Currently, there are an increasing number of studies on the use of machine learning methods for diagnosis of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…In a study for prediction of the incidence of malaria, researchers used a new back-propagation neural network (BPNN) classification model. They showed that BPNN model was well suited for deciphering the risk of acquiring malaria as well as other infectious diseases [ 64 ]. Currently, there are an increasing number of studies on the use of machine learning methods for diagnosis of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…During the training process in the BPNN model, the error should meet the pre-set accuracy requirements. The weights between the neurons will be adjusted automatically along the reverse direction of the BPNN until the minimum network error up to the criterion [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have explored the use of statistical ML models to categorize a person’s chats and texts as exhibiting either depressive or non-depressive behavior by analyzing patterns in language use and to identify features that are indicative of depression [ 14 , 15 ]. As observed before, ML models suffer from poor performance due to their inability to handle the non-linearity of risk predictors and gold standard labels or events [ 13 , 16 , 17 ]. Similarly, the linear structure architecture of current automated depression detection models renders them susceptible to poor performance, since they only focus on individual words and fail to consider the context of previous and subsequent words.…”
Section: Introductionmentioning
confidence: 99%